Exploring contractile protein mechanisms and target medications for cardiomyopathic patients with diastolic dysfunction - Dustin Gerber; Junjun Quan; Bo Pan; Xupei Huang; Jie Tian (Wiley, 2024)
Abstract Genetic defects have been increasingly found in cardiomyopathies, which are often present with mutations in cardiac contractile proteins. These congenital defects involve numerous intracellular pathways and share several critical clinical features, such as systolic or diastolic dysfunction fostering the various cardiomyopathic phenotypes. Hypertrophic cardiomyopathy and restrictive cardiomyopathy (RCM) share a common pathological feature, that is, diastolic dysfunction. Studies have shown that mutations of contractile proteins, especially myosin heavy chain and troponin, are tightly associated with diastolic dysfunction in patients with Cardiomyopathies (CMs), including pediatric patients with CM. Therapeutics, including green tea extract (epigallocatechin gallate) and mavacamten, interact directly with these contractile proteins and have shown promising results. This article will review recent and contemporary research on diastolic dysfunction in CMs, especially hypertrophic cardiomyopathy and RCM, which include their target proteins, mechanisms, clinical diagnosis, and potential therapies.